Genetic polymorphisms in the MMP-1 and MMP-3 gene may contribute to chronic periodontitis in a Brazilian population - Astolfi, Claudia Maria; Shinohara, André Luís; Da Silva, Rodrigo Augusto; Santos, Maria Cristina Leme Godoy; Line, Sergio Roberto Peres; De Souza, Ana Paula (Journal of clinical periodontology, 2006)
Objectives: Matrix metalloproteinase‐1 and ‐3 (MMP‐1, MMP‐3) represent proteinases that degrade macromolecules of the extracellular matrix. These enzymes play a fundamental role during destruction of periodontal tissues. Genetic polymorphisms were characterized in the promoter region of the MMP‐1 and MMP‐3 genes. The aim of this study was to investigate the relationship between these genetic variations with chronic periodontitis in a Brazilian population. Material and Methods: Non‐smoking subjects (n=114) exhibiting sites 5 mm clinical attachment loss were recruited for study. Control subjects (n=109) should not exhibit clinical signals of periodontitis. MMP‐1 (−1607 1G/2G, −519 A/G) and MMP‐3 (−1612 5A/6A) gene promoter polymorphisms were genotyped using PCR‐RFLP methods. Results: Analysis of polymorphisms showed no differences in distribution of the −1607 1G/2G and −519 A/G variants in the MMP‐1 gene between the healthy and periodontitis group (p>0.05). However, the distribution of genotype frequencies of the −1612 5A/6A polymorphism in the MMP‐3 gene showed that the 5A/5A genotype was significantly more frequent in the periodontitis group (p=0.008). The same was not observed in the 5A/6A genotype once only one 5A allele is carried. We also observed a trend to increase the frequency of the MMP‐1/MMP‐3 haplotype (2G/5A) in the periodontitis group (p=0.08). Conclusion: On the basis of the results, no significant association is found for the MMP‐1 polymorphisms with susceptibility of periodontitis, while the MMP‐3 gene polymorphism may contribute to periodontal tissue destruction during periodontitis in Brazilian subjects.